Perlecan in the Natural and Cell Therapy Repair of Human Adult Articular Cartilage: Can Modifications in This Proteoglycan Be a Novel Therapeutic Approach? - John Garcia; Helen S. McCarthy; Jan Herman Kuiper; James Melrose; Sally Roberts (Biomolecules, 2021)
Articular cartilage is considered to have limited regenerative capacity, which has led to the search for therapies to limit or halt the progression of its destruction. Perlecan, a multifunctional heparan sulphate (HS) proteoglycan, promotes embryonic cartilage development and stabilises the mature tissue. We investigated the immunolocalisation of perlecan and collagen between donor-matched biopsies of human articular cartilage defects (n = 10 × 2) that were repaired either naturally or using autologous cell therapy, and with age-matched normal cartilage. We explored how the removal of HS from perlecan affects human chondrocytes in vitro. Immunohistochemistry showed both a pericellular and diffuse matrix staining pattern for perlecan in both natural and cell therapy repaired cartilage, which related to whether the morphology of the newly formed tissue was hyaline cartilage or fibrocartilage. Immunostaining for perlecan was significantly greater in both these repair tissues compared to normal age-matched controls. The immunolocalisation of collagens type III and VI was also dependent on tissue morphology. Heparanase treatment of chondrocytes in vitro resulted in significantly increased proliferation, while the expression of key chondrogenic surface and genetic markers was unaffected. Perlecan was more prominent in chondrocyte clusters than in individual cells after heparanase treatment. Heparanase treatment could be a means of increasing chondrocyte responsiveness to cartilage injury and perhaps to improve repair of defects.